Structural Design of General Hospital in Nablus - Juhba, Sameh; Jweiles, Midhat; Jabari, Qasem; Tartory, Yousef; Sider, Mahmoud (جامعة بوليتكنك فلسطين - مباني, 2016)
The idea of this project is the structural design of general hospital in Nablus. The project has been developed to contain all the necessary requirements to work as a typical hospital, where there is a sufficient number of bedrooms, offices, nurses and doctors bedrooms, pharmacy, mechanical and electrical rooms, obstetrics and gynecology and all services needed. The project design provides optimal architectural and structural solutions, so that it is taking into account the aesthetic and functional purposes and provides comfort use. The project will include the construction elements of slabs, beams, columns, and foundations. The building consists of eight floors including basement floor with a total area of 39000 m2 approximately. The design will be based on the requirements of the American Code (ACI -318- 08)[1], and the Jordanian Code of loads, and we will use some of software like (latex) and (AutoCAD 2015) to project output, and also we use some of programs for structural design and analysis like, Atir, Safe. After completion of the project we expect to be able to provide structural design of all the structural elements of the project accordance to the requirements of the code.
no of pages 103 , مباني 19/2016
Keywords: التصميم الإنشائي; Hospital Buldings